Pain catastrophizing moderates the relationship between chronic pain and insomnia severity in persons with opioid use disorder - Baime, Melanie A.; Satyavolu, Prem Umang; Huhn, Andrew S.; Ellis, Jennifer D. (Frontiers in Sleep, 2023)
Study objectives. Chronic pain and insomnia commonly co-occur among individuals with opioid use disorder (OUD) and are associated with adverse treatment outcomes and reduced quality of life. Exploring factors that influence these relationships may help identify relevant treatment targets. The present study investigated whether pain catastrophizing moderates the presence of chronic pain and insomnia severity in individuals with OUD. Methods. Participants with OUD symptoms (N = 154) were recruited from Amazon’s Mechanical Turk, and completed screening measures for chronic pain, insomnia, and pain catastrophizing. Moderation analyses were used to explore whether pain catastrophizing moderated the relationship between chronic pain and insomnia severity. Results. Results suggested that chronic pain was only associated with insomnia severity symptoms among individuals with higher levels of pain catastrophizing but was unrelated at lower levels of pain catastrophizing. Conclusions. These results suggest that pain catastrophizing may represent a modifiable risk factor among individuals with co-occurring OUD, insomnia, and chronic pain. Future longitudinal and experimental research that examines changes in insomnia, pain severity, and pain catastrophizing over time in OUD may be beneficial.